2020
DOI: 10.1101/2020.04.03.20043992
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anxiety, worry and perceived stress in the world due to the COVID-19 pandemic, March 2020. Preliminary results

Abstract: Introduction:Since the beginning of the outbreak in China, ending 2019, the Novel Coronavirus has spread subsequently to the rest of the world causing an ongoing pandemic. The World Health Organisation (WHO) declared COVID-19 "a public health emergency of international concern." Taking into consideration the lockdown and quarantine situation, a research team of doctors from the Hospital of Salamanca, decided to do an evaluation of the current emotional state on the general population with a webbased survey in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
88
8
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(144 citation statements)
references
References 19 publications
(17 reference statements)
25
88
8
6
Order By: Relevance
“…Anxiety has a signi cant negative correlation with age (r = -.331, p <.01) so that the more mature age, anxiety tends to be lower. This nding is supported by previous research which state older individuals show low levels of anxiety (Limcaoco et al, 2020). (Frazier et al, 2019) emphasize that there are three components that can explain decision making in older individuals, namely theory of mind, regulation of emotions and memories of past experiences.…”
Section: Data Collection Uses a Likert Scale Consisting Of The Awarensupporting
confidence: 75%
See 1 more Smart Citation
“…Anxiety has a signi cant negative correlation with age (r = -.331, p <.01) so that the more mature age, anxiety tends to be lower. This nding is supported by previous research which state older individuals show low levels of anxiety (Limcaoco et al, 2020). (Frazier et al, 2019) emphasize that there are three components that can explain decision making in older individuals, namely theory of mind, regulation of emotions and memories of past experiences.…”
Section: Data Collection Uses a Likert Scale Consisting Of The Awarensupporting
confidence: 75%
“…In Lee, (2020) showing that younger adults have more anxiety about COVID-19. (Limcaoco et al, 2020) also said that older individuals showed lower levels of anxiety even though this group was reported as having a high risk of contracting COVID-19 while young adult individuals had higher stress levels because they showed concern about being infected with COVID-19.…”
Section: Anxietymentioning
confidence: 99%
“…Research regarding the emotions and mental health in the context of infectious diseases is still scarce. Yet, one of the researched emotions linked with mental health during the pandemic is regret (Limcaoco et al, 2020). Regret is an emotional experience elicited when an individual is unsatis ed with the acquired outcome among the possibility of better options (Shepherd & O'Carroll, 2014).…”
Section: Self-blame Regret and Mental Healthmentioning
confidence: 99%
“…Considering the fast transmission of the virus between humans, high mortality rates and strict prevention measures including travel bans, home con nements, social distancing, compulsory face mask wear, school suspensions, this time of global crisis is characterized with strong negative emotions and deteriorated mental health. Several studies reported the heightened negative affectivity symptoms due to the pandemic (Limcaoco et al, 2020) and documented that COVID-19 pandemic exacerbated mental health issues including depression across the world (Bäuerle et al, 2020;Choi, Hui & Wan, 2020;Nickell et al, 2004;Tsang, Scudds, & Chan, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Another early pandemic response study examining stress levels of individuals in different countries around the world from March 17 to April 1, 2020, found that on average, individuals reported being moderately stressed. 12 Factors associated with signi cantly higher scores included identifying as female, young age, being a student, expressing concerns about virus contraction, and feeling susceptible to the coronavirus. Additionally, healthcare workers have reported more severe levels of anxiety, depression, insomnia, and somatization symptomologies during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%